A diabetes peer support intervention that improved glycemic control: mediators and moderators of intervention effectiveness. (December 2013) - Piette, John D; Resnicow, Ken; Choi, Hwajung; Heisler, Michele
Objective: In a randomized trial, a guided diabetes peer support intervention improved glycemic control (A1c), with a difference in A1c change between groups of 0.58% ( p = 0.004). The current study examined whether improvements in insulin uptake and perceived diabetes social support mediated the intervention's impact on A1c. We also examined potential moderation by patients' health literacy, diabetes social support, or diabetes distress. Methods: We conducted secondary analyses for 212 type 2 diabetes patients participating in the trial using accepted methods for testing mediation and moderation effects. Results: Roughly half (49%, 95% CI: 3–80%) of the A1c effect was mediated by increased insulin use, while changes in diabetes social support had a negligible impact. A1c impacts varied across subgroups defined by baseline diabetes social support and functional health literacy (both p < 0.01). The intervention was particularly beneficial among patients with low baseline diabetes support or literacy levels. The intervention had a greater impact on A1c among patients with more frequent engagement in peer support calls ( p < 0.01). Discussion: Patients receiving increased peer support had improved glycemic control largely due to their greater likelihood of initiating insulin. Greater intervention engagement was associated with stronger effects. The intervention had its greatest benefits among patients with low support or poorer health literacy.